Queering Protracted Displacement: Lessons from Internally Displaced Persons in the Philippines - Quintero, Romeo Joe; Hari, Amrita (Anti-Trafficking Review, 2022)
In this short paper, we apply a queer lens to challenge the current parameters of protracted refugee situations (PRS), as outlined in international legal instruments, by drawing on stories of internally displaced persons (IDPs) in the Philippines affected by the Zamboanga Siege in 2013. We argue that PRS is not a status that displaced individuals transition in and out of, and that the reliance on nation-states to implement international protections can exacerbate the already tenuous situations of IDPs. The perception of prolonged displacement lingers well beyond traditional durable solutions of return, local integration, and resettlement, shaping IDPs’ longing for home.